Political Science, should it care about what is going on? - Chaves Giraldo, Pedro (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
Tocqueville's 1835 statement that "we need a new political science for a new world" is now extremely topical. The substantial changes brought about by three decades of neoliberalism have radically altered the processes, structures, and actors that political science studies. Among the results to be considered: a democratic regression unprecedented since the end of the Second World War. The symptoms of this democratic malaise are exemplified by the electoral growth of extreme right-wing parties across the globe, although in this paper we will focus on Europe. The consolidation of so-called illiberal democracies is a manifestation of this slow and silent decomposition of democracy. Political science has had democracy, its defence and improvement, as a central objective of its discipline since its birth; indeed, its vitality and independence is related to the vitality and quality of democracy itself. In the article we argue that there is no true Political Science apart from the democratic condition and quality of our political systems. The different models of authoritarianism end up turning Political Science into a technique of power management. In this context, the contributions of political theory may be of the utmost importance at this point in time.
Keywords: Political science; democracy; crisis